Service of Personal Adjutant to the President of Lithuania in the 1920s–1930s - Jakubavičienė, Ingrida (History / Istorija, 2019)
The article analyses the activities of six Lithuanian military officers who served as the adjutants to the President of the Republic of Lithuania in the 1920s–1930s. The article reveals short biographies of adjutants Pranas Tamašauskas, Aloyzas Valušis, Tadas Šakmanas, Vaclovas Šliogeris, Stepas Žukaitis and Jonas Mikaliūnas, their duties and the relationship with the President. The article is based on historical documents, historiography, published memoirs of adjutant Vaclovas Šliogeris and other materials.